2017
DOI: 10.1177/1028315317720767
|View full text |Cite
|
Sign up to set email alerts
|

English-Medium Instruction and Intercultural Sensitivity: A Korean Case Study

Abstract: This case study examined the reactions of local students to the diversity in student population. Specifically, it investigated how the local students’ intercultural sensitivity to the international students is interrelated with their perception of the English-medium instruction (EMI) policy. The quantitative and qualitative analyses of the questionnaire responses of 213 college students and the subsequent interviews with 15 students revealed a lack of intercultural sensitivity which was correlated with their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A third challenge is the increasing prevalence of EMI in non-native speaking contexts, as issues have been raised about English competency and comfort of existing students/staff (Kim, Choi, & Tatar, 2017). A systematic review of 83 EMI studies outlined concerns from students/staff and found inconclusive evidence on the overall benefits to language or content learning (Macaro, Curle, Pun, An, & Dearden, 2017).…”
Section: Challenges Related To Internationalised Academic Contentmentioning
confidence: 99%
“…A third challenge is the increasing prevalence of EMI in non-native speaking contexts, as issues have been raised about English competency and comfort of existing students/staff (Kim, Choi, & Tatar, 2017). A systematic review of 83 EMI studies outlined concerns from students/staff and found inconclusive evidence on the overall benefits to language or content learning (Macaro, Curle, Pun, An, & Dearden, 2017).…”
Section: Challenges Related To Internationalised Academic Contentmentioning
confidence: 99%
“…In addition to learning a good foreign language, you must know foreign cultures and familiarize the diff erences between cultures. You must have the necessary language skills and intercultural communication skills (Kim, Choi, & Tatar, 2017). The foreign language teaching in China has undergone a series of reforms, but the teaching eff ect has always been unsatisfactory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In comparison to the European context, EMI studies in Asian countries are much fewer. The current literature tends to be framed, most often implicitly, within Kachru's (1976) Three Circles model of world Englishes by limiting the research scope to: (1) potential challenges or deficiencies with regards the English language proficiency of non‐native English instructors in the EMI programmes situated in Expanding Circle countries (that is, non‐English‐speaking and not being previous colonies of English‐speaking countries like Great Britain) (Hu & Lei, 2014); (2) the role of L1 and code‐switching practices of non‐native English‐speaking instructors in EMI classrooms (An & Chiang, 2015; Gu & Lee, 2018; Kim, Choi, & Tatar, 2017); (3) comparisons between EMI and CMI (Chinese‐medium instruction) policies and curricula (Zhang, 2018; Zhao & Dixon, 2017); and (4) the likeliness of EMI programmes to empower students with the accumulation of relevant symbolic and cultural capital and enhancing competitiveness in the global human resource market (Gu & Lee, 2018; Hu, 2008, 2009). A few studies have also investigated EMI practices and intercultural sensitivity of local/international students as influenced by their perceptions of the EMI policy, whereas the notion of culture is discussed as a nation‐bound entity characterized by essentialist features (An & Chiang, 2015).…”
Section: Introductionmentioning
confidence: 99%